Grain Boundary Migration Induced by a Magnetic Field: Fundamentals and Implications for Microstructure Evolution - Molodov, Dmitri A (Microstructural Design of Advanced Engineering Materials, 2013)
In this chapter, an overview of the recent research on magnetically affected grain boundary dynamics and microstructure evolution in nonferromagnetic materials is presented. Grain boundary migration can be induced by a magnetic field, if the anisotropy of the magnetic susceptibility generates a gradient of the magnetic‐free energy density across the boundary. In contrast to curvature‐driven boundary motion, a magnetic driving force also acts on planar boundaries so that the motion of crystallographically fully defined boundaries can be investigated. Since the magnetic force does not depend on boundary properties, that is, its energy and shape, and the true grain boundary mobility can be determined. The results of migration measurements obtained on bismuth and zinc bicrystals are addressed. Investigations on polycrystalline cold‐rolled zinc, titanium, and zirconium revealed that magnetic annealing can cause significant changes in the evolution of the microstructure with respect to the grain size, orientation distribution, and grain topology. Therefore, a magnetic field can be effectively utilized as an additional degree of control of texture and microstructure development in nonferromagnetic polycrystals.